Low birth weight in Spain associated with sociodemographic factors. Issue 1 (February 1995) - Rodríguez, C; Regidor, E; Gutiérrez-Fisac, J L
Abstract : STUDY OBJECTIVE–To describe the effect of different social and demographic characteristics on low birth weight (LBW) (less than 2500 g) in Spain, in both preterm (less than 37 weeks' gestation) and term infants (between 37 and 42 weeks' gestation). DESIGN–The study used data obtained from the Spanish birth registry. SETTING–The study was based on those live born infants registered in 1988 from provinces where the birthweight details were completed in at least 99.5% of the birth registration records. PARTICIPANTS–A total of 1332 preterm LBW infants, 1292 term LBW infants, and 38, 967 controls were included in the study. MEASUREMENTS AND MAIN RESULTS–The odds ratio (OR) calculated by logistic regression was used as the measure of association between LBW and the sociodemographic variables. The highest ORs of preterm LBW were found in mothers younger than 20 years (1.32; 95% CI 0.98, 1.77) and older than 34 years (1.28; 95% CI 1.04, 1.59), in unmarried mothers (1.68; 95% CI 1.36, 2.07), and in fathers with manual occupations (1.26; 95% CI 1.08, 1.46). In term, live born infants the highest ORs were found in adolescent mothers (1.63; 95% CI 1.25, 2.14), in first born live born infants (1.38; 95% CI 1.09, 1.74) or the fourth born or more (1.28; 95% CI 0.91, 1.80), in unmarried mothers (1.55; 95% CI 1.27, 1.90), in housewives (1.13; 95% CI 0.99, 1.29), and in fathers with manual occupations (1.21; 95% CI 1.04, 1.42). CONCLUSIONS–The results have allowed documentation of the risk of preterm and term LBW in various age and social groups in Spain.